Materiais híbridos orgânicos-inorgânicos: argilominerais, óxidos e polímeros - CAVALCANTE, Manoella da Silva (Universidade Federal do Pará, 2018)
The interaction on a nanometric scale of molecular or polymeric species with inorganic substrates constitute the basis for obtaining hybrid materials. The development of these materials represents an emerging and interdisciplinary topic between the frontiers of life sciences, materials and nanotechnology. The combination of these two materials, organic-inorganic, produces a new material with improved properties and structures essentially different from its individual components. Constituted by a continuous phase (matrix), being plastics or cellulose, and an inorganic phase, such as clay minerals or oxides. several papers have been published obtaining these materials with improved properties: traction modules, gas barrier, flame retardants, density, melt strength, electrical conductivity, etc. Capable of making industry flexible and rigid products and in the manufacture of electronic materials (wire and cable coatings manufacture of sensors / actuators), vaccine production, among others. The most clay minerals used in the synthesis of hybrid materials are the species montmorillonite, clay but others can also be used, such as illite and palygorskita. In the state of Maranhão, northeastern Brazil, there are several occurrences of clay minerals, most notably smectite, illite and palygorskite. Among these clay minerals two new occurrences have already been identified and characterized by the UFPA Group of Applied Mineralogy (GMA), such as Bentonite Formosa and Palygorskite, which are abundant in the region and do not yet have an application. In addition to a new occurrence of illite not yet characterized in the region of the municipality of Barão de Grajaú (MA). Another material with great potential for obtaining nanomaterials is the vanadium pentoxide, having intrinsic features such as alignment of the magnetic field, and redox system such as gel elasticity, enabling application in the electronics industry for the manufacture of batteries and electrochromic displays for sensors/actuators. In Brazil, vanadium pentoxide began to be produced in 2014 by Maracás S/A. Currently, its consumption is focused on the production of special steels for the manufacture of aircraft structures and the aerospace industry. At the national level the production and development of hybrid materials and platforms for use in high-tech industry is small. Thus, the development and improvement of nanomaterials is necessary using as starting material and clay minerals national occurrence oxides. Within this context, this thesis aimed to develop a study on application of three clay minerals (Mg-montmorrillonite, illite and Palygorskita) from northeastern Brazil, besides vanadium pentoxide in the processing of hybrid materials using as poly matrix (methylmethacrylate) (PMMA ) and cellulose nanofibers. For this, the methodology of this work was divided into three parts: The first one consisted of the collection or synthesis, treatment and characterization of the individual materials (clay minerals, vanadium pentoxide, methyl poly (methacrylate) and cellulose). The second was to obtain hybrid materials clay mineral-PMMA (AP) and vanadium pentoxide cellulose (VC) and the third one was mainly to evaluate the thermal and mechanical properties of the AP hybrids and the electrochromic properties of the VC films. The characterization of the samples confirmed the predominance of Mg-montmorillonite, Illita and Palygorskita. The natural clay and organophilic fraction were used to obtain 12 samples with common and elastomeric PMMA to perform the physical-chemical tests focusing mainly on flammability and traction. By means of XRD measurements it was possible to verify that there was interaction between the two organic-inorganic phases, and that in the elastomeric PMMA there was a better dispersion of the clay minerals. The tests carried out on these materials indicated that the hybrids exhibit intrinsic thermal and mechanical behavior of each material possibly related to the type of structure present in the inorganic phase, contributing to the increase or decrease of Tg, Tm, flammability and traction. Four V2O5-cellulose films were obtained and characterized. Electrochromic tests were conducted in the films that presented better performance. It was possible to verify that there was interaction between the nanofibers of vanadium pentoxide and cellulose maintaining the electrochromic property of the oxide. Potentiometric measures were found that after 30 and 100 cycles the films remained flexible and maintained their properties. In this way, this work concluded that it is possible to obtain hybrid materials with clay minerals coming from the northeastern region of Brazil and can adapt their thermal and mechanical properties according to their application. The same was observed for the VC films that presented satisfactory results and that can be used in displays and / or flexible sensors.